Immunohistochemical Study of Estrogen, Progesterone Receptor and Her-2neu Oncogene with Her-2neu Biomarker Estimation by ELISA Technique in Primary Breast Cancer before Chemical Therapy - Al-Khafaji, Ali; Fadhil, Ayad; Hameed, Mohammed (Iraqi Journal of Science, 2023)
Breast cancer is one of the comments malignant tumors worldwide especially in Iraq; it is a leading cause of death in Iraqi women. Determination of estrogen and progesterone receptors status is helpful in selecting the patients most likely to receive benefit from endocrine therapy, and provide prognostic information on recurrence and survival since their expression is related to the degree of the tumor differentiation. From November 2012 to March 2013, 150 breast cancer patients at Al-Amal Hospital in Baghdad were attended to start treatment of disease for the first time. All patients included in this study did not receive chemotherapy. Patients were asked to bring their paraffin embedded tissue blocks to participate in estrogen, progesterone and Her-2/nue receptors estimation. Blood samples were also collected from the patients to estimate positive Her-2nue cases in serum. Age distribution in women with breast cancer showed that 44%of cases at age group (40 – 49) years. 23% of the patients had a positive family history (first and second degree). Histological types of breast carcinoma showed that 82%, 14% and 4% were ductal, lobular and mixed carcinoma respectively. The Makee classification showed that Grade I, II, and III were detected in 10%, 64% and 26% respectively. TNM staging revealed that 16% of the patients were recorded in stage I, 44% in stage II, 32% in stage III and 8% in stage IV. It was demonstrated that 72% and 70% of breast carcinomas were positive for ER and PR respectively; both markers correlated with age, family history, type, histological grade and stage of the disease. Her-2/neu showed 28% expression in Iraqi breast cancer cases. HER2/neu over-expression (>15 ng/ml) was observed in 36 out of 150 patients (24%) Her-2/neu serum level at ELISA diagnosis and in 42 out of 150 (28%) at immunohistochemistry method (IHC).There were significant (P <0.001) association between tissue HER-2/neu and serum HER-2 levels. Detection Her-2/neu in serum by ELISA technique could be used as a method for detection with high rate reached to 78% after mastectomy, also it considered as an excellent method for follow up.